Spectral Coexistence of MIMO Radar and MIMO Cellular System - Mahal, Jasmin A.; Khawar, Awais; Abdelhadi, Ahmed; Clancy, T. Charles (IEEE transactions on aerospace and electronic systems, 2017)
This paper details designing the precoder of a MIMO-radar spectrally-coexistent with a MIMO cellular system. Spectrum sharing with zero or minimal interference is achieved by using, respectively, the conventional switched null space projection (SNSP) or the newly proposed switched small singular value space projection (SSSVSP). Loss in radar target localization capability due to precoding can be compensated by using SSSVSP instead of SNSP to some extent but increasing the number of radar antenna elements is more effective.